2002
DOI: 10.1080/03014223.2002.9518298
|View full text |Cite
|
Sign up to set email alerts
|

Home range, territorial behaviour and habitat use of stoats (Mustela erminea) in a colony of Hutton's shearwater (Puffinus huttoni), New Zealand

Abstract: We investigated home range size, territorial behaviour and habitat use of stoats in a colony of Hutton's shearwaters. A total of 15 stoats were caught, and radio-tracking data were obtained from 11 of them. Stoats tracked during the summer had very small home ranges (males 16.0 ha, females 9.4 ha), and with the exception of two immature animals, were defending intrasexual territories. Two males tracked in the spring had larger home ranges (47.9 ha) and were not territorial. Stoats showed a strong preference fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…When large mast crops are available to martens, animals encountering traps may be satiated thereby reducing the attractiveness of a baited trap. Inverse relationships between food availability and trapping vulnerability have been previously documented in other mustelids (Alterio et al 1999, Cuthbert and Sommer 2002, King and White 2004).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…When large mast crops are available to martens, animals encountering traps may be satiated thereby reducing the attractiveness of a baited trap. Inverse relationships between food availability and trapping vulnerability have been previously documented in other mustelids (Alterio et al 1999, Cuthbert and Sommer 2002, King and White 2004).…”
Section: Discussionmentioning
confidence: 66%
“…Thompson and Colgan (1987) documented large increases in home range size during a period of prey declines; males and females increased the size of their home ranges 2.0–2.2× and 4.1–4.3×, respectively, compared with years when prey was abundant. Similarly, Murphy and Dowding (1995) and Cuthbert and Sommer (2002) found that short‐tailed weasels (stoats) maintained small home ranges at high prey densities. In contrast to these studies, Payer et al (2004) investigated marten home range fidelity ( n = 131 animals) and found that mean seasonal fidelity was 67.4% for winter locations occurring in home ranges from the previous summer.…”
Section: Discussionmentioning
confidence: 89%
“…Stoats Mustela erminea , like many other mustelids, are sexually size dimorphic. In the temperate zone, the mean body weight of females is on average 61% that of males (Erlinge, 1977; King, 1989 and references therein; Cuthbert & Sommer, 2002), and in boreal areas (northern Sweden, 63°N) the size difference can be even larger (53%; Erlinge, 1987). The difference is supposedly caused by specialization on different prey to avoid intersex competition (Brown & Lasiewski, 1972) or different reproduction strategy between sexes (Erlinge, 1979; Moors, 1980; Sandell, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…As food resources in Orkney are relatively high and stable it was appropriate to assume that stoats maintain smaller home ranges (Cuthbert and Sommer, 2002;Veale et al, 2015;Anderson et al, 2016). Following this, we modified Model S4 by changing the values of sigma (Model S5).…”
Section: Simulation Model (Model S4)mentioning
confidence: 99%